Cross-sectional and Prospective Correlates of Recovery Expectancies in the Rehabilitation of Whiplash Injury. Issue 4 (April 2018) - Elphinston, Rachel A.; Thibault, Pascal; Carriere, Junie S.; Rainville, Pierre; Sullivan, Michael J.L.
Abstract : Objectives: Investigations have shown that expectancies are significant prognostic indicators of recovery outcomes following whiplash injury. However, little is currently known about the determinants of recovery expectancies following whiplash injury. The purpose of the present study was to examine the cross-sectional and prospective correlates of recovery expectancies in individuals admitted to a rehabilitation program for whiplash injury. Materials and Methods: Participants (N=96) completed measures of recovery expectancies, psychosocial variables, symptom severity, symptom duration, and disability at time 0 (admission) and time 1 (discharge). Results: Consistent with previous research, more positive recovery expectancies at time 0 were related to reductions in pain at time 1 ( r =−0.33, P <0.01). Scores on measures of pain catastrophizing, fear of movement and reinjury, and depression were significantly correlated with recovery expectancies. Pain severity, duration of work disability, and neck range of motion were not significantly correlated with recovery expectancies. Over the course of treatment, 40% of the sample showed moderate to large changes (an increase of ≥20%) in recovery expectancies, there were small changes (<20%) in 30% of the sample, and negative changes in 20% of the sample. A hierarchical regression showed that decreases in fear of movement and reinjury (β=−0.25, P <0.05) and pain catastrophizing (β=−0.23, P <0.05) were associated with increases in recovery expectancies through the course of treatment. Conclusions: The discussion addresses the processes linking pain-related psychosocial factors to recovery expectancies and makes recommendations for interventions that might be effective in increasing recovery expectancies.